The Effectiveness of Implementation of Competency-Based Training at the UPTD Vocational Training Center (BLK) of West Sulawesi Province - Nurmillah Nurmillah; Andi Farid Kusno; A.M. Azhar Aljurida; Dahlan Dahlan; Beddu Lahi; Harniati Harniati (Program Pascasarjana Universitas Negeri Makassar, 2023)
The purpose of this study was to determine the effectiveness of competency-based training in improving skills and human resources in West Sulawesi Province. This study uses qualitative research methods, the data used are primary data obtained from interviews with UPTD employees of West Sulawesi Province instructors, assessors/competence test examiners through professional certification institutions/LSP Makassar and training participants in vocational fashion and vocational computer/ICT , secondary data obtained from agencies related to research in this case the UPTD Vocational Training Center of West Sulawesi Province, observation and documentation methods, data analysis method used is descriptive qualitative. The results of this study indicate that the role of the UPTD BLK in West Sulawesi Province in improving the skills and human resources of the community in West Sulawesi has not been maximally effective in reducing unemployment. This can be seen from the analysis of the data in table 2.4 and the explanation of the results of the research. It turns out that in 2020-2022 the number of participants UPTD BLK training in West Sulawesi Province has not been fully absorbed in the world of work. Keywords : Improvement of skills and human resources greatly influences the effectiveness of competency-based training.